Distractor Ignoring: Strategies, Learning, and Passive Filtering. (December 2019) - Geng, Joy J.; Won, Bo-Yeong; Carlisle, Nancy B.
Our sensory environments contain more information than we can process, and successful behaviors require the ability to separate task-relevant information from task-irrelevant information. Much research on attention has focused on the mechanisms that result in selection of desired information, but much less is known about how distracting information is ignored. Here, we describe evidence that strategic, learned, and passive information can all contribute to better distractor ignoring. The evidence suggests that there are multiple ways in which distractor ignoring is supported, and these ways may be different from those of target selection. Future work will need to identify the mechanisms by which each source of information adjusts attentional priority such that irrelevant information is better ignored.